EFEKTIVITAS MINYAK CENGKEH TERHADAP PATOGEN YANG BERASOSIASI DENGAN TANAMAN TOMAT (Lycopersicum esculentum Mill.) - PADDA, PUTRI MEGAYANTI; TAUFIK, MUHAMMAD; ASNIAH, ASNIAH; BOTEK, MUHAMMAD; RAHMAN, ABDUL; GUNAWATY, GUSNAWATY HS; MARIADI, MARIADI (Jurnal Agroteknos, 2022)
This study aimed to evaluate the effect of clove oil to control pathogens associated with tomato plants in screen houses. The study was carried out using a completely randomized design (CRD) with 5 treatments repeated 3 times and each treatment consisted of 3 plants for a total of 45 plants, the treatments given were P0 (without application), P1 (pathogenic fungus Sclerotium sp. without clove oil application). , P2 (pathogenic fungus Sclerotium sp. with clove oil application), P3 (pathogenic fungus Helminthosporium sp. without clove oil application), P4 (pathogenic fungus Helminthosporium sp. clove oil application). The variables observed were plant height, stem diameter, number of branches and disease severity of tomato plants. The results showed that clove oil was able to increase plant growth as indicated by the highest average height and diameter of 18.61cm and 0.31cm, respectively. Clove oil application also suppressed the development of the pathogen Sclerotium sp. As indicated by the average incubation period and disease severity 18.67 days and 6%, respectively.